2022
DOI: 10.1002/hbm.26111
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude modulating frequency overrides carrier frequency in tACS‐induced phosphene percept

Abstract: The amplitude modulated (AM) neural oscillation is an essential feature of neural dynamics to coordinate distant brain areas. The AM transcranial alternating current stimulation (tACS) has recently been adopted to examine various cognitive functions, but its neural mechanism remains unclear. The current study utilized the phosphene phenomenon to investigate whether, in an AM‐tACS, the AM frequency could modulate or even override the carrier frequency in phosphene percept. We measured the phosphene threshold an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Additionally, the selection of the electrode montage, specifically the placement of electrodes, can significantly alter the outcomes of tACS. Hsu et al reported that facial stimulation montage predominantly produced phosphenes in the upper-left visual field, whereas using the occipital montage led to a more uniform distribution of phosphenes throughout the visual field ( 29 ). These studies inspired us to further investigate optimizing these parameters to achieve desired neural outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the selection of the electrode montage, specifically the placement of electrodes, can significantly alter the outcomes of tACS. Hsu et al reported that facial stimulation montage predominantly produced phosphenes in the upper-left visual field, whereas using the occipital montage led to a more uniform distribution of phosphenes throughout the visual field ( 29 ). These studies inspired us to further investigate optimizing these parameters to achieve desired neural outcomes.…”
Section: Introductionmentioning
confidence: 99%